Cross Cultural Rhetoric Awareness of Undergraduate Thesis Introduction Section Written by Acehnese EFL Students - Usman, Bustami; Rizkanisa, Novalia; Samad, Iskandar Abdul; Muslem, Asnawi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
Abstract: This study investigated cross cultural rhetoric awareness of introduction section by Acehnese EFL students. This study aimed at describing the rhetorical pattern and determine the cross cultural rhetoric awareness by looking at the rhetorical pattern in Introduction section. A qualitative method and content analysis were used in this study which analyzed the Introduction section. The data of this research was English undergraduate thesis written by ten Acehnese students as the documentation was applied as the instrument. The data were collected from two Islamic institutes in Aceh. The research was conducted by using documentation analysis. The result of the analysis demonstrated that the English writings by Acehnese students maintained the inductive style and the idea of the paragraph is circular. However, the use of markers is enough to be considered. The conclusion led to the rhetorical pattern of the Acehnese students which is in oriented style. Indeed, the implication of the finding showed that the studentsâ cross cultural rhetoric awareness toward English writing convention, especially in academic writing, is low